Pola Interaksi Edukatif dalam Metode Pembelajaran di Pesantren Khozinatul ‘Ulum Blora - Hamdan Adib (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2021)
As one of the educational institutions in Indonesia, Islamic boarding schools also have methods in conveying material to their students and sometimes this method is a characteristic found in Islamic boarding schools. These various methods should be understood by taking into account the various patterns contained in them so that it can be seen to what extent the pesantren is actively involved in fostering good interaction between the kiai and the santri. The purpose of this study is to determine the pattern of educative interactions contained in the learning method at the Khozinatul 'Ulum Blora Islamic boarding school. This research is a field research carried out at the Khozinatul 'Ulum Blora Islamic Boarding School, the data collection techniques used are semi-structured interviews, participatory observation, and also documentation. The data obtained were then analyzed using Miles and Huberman's theory, namely data reduction, data display and data verification. The results of this study indicate that at the Khozinatul 'Ulum Blora Islamic boarding school in teaching material to students using five methods, namely memorization in which there is a two-way interaction pattern, bandongan in which there is a one-way interaction pattern and in the bahsul masa'il method, practice and play. role in which there is a pattern of multi-directional interaction.